“You Want Me To Do What?” The Benefits of Co-teaching in the Middle Level - Ellis Hurd; Gary Weilbacher (Middle Grades Review, 2017)
Exemplary middle schools use interdisciplinary teaming which often involves some level of co-planning, co-teaching, and co-assessing. In addition to this collaborative foundation, federal mandates for supporting students have led to frequent co-teaching between special educators, bilingual/bicultural specialists, and regular classroom teachers. Given that middle level educational frameworks, current inclusion practices, and demands for differentiation are all dependent upon teachers working together, increasing the presence of co-teaching within middle level teacher education program is both pragmatically sound and connected to foundational theories of middle level education. Middle school teachers and university faculty members who engage in co-teaching with teacher candidates can provide candidates with practical experiences tied closely to the work that will be expected of them as public school teachers. Early exposure to co-teaching models can better equip our students for their future work in today’s schools. This study highlights the benefits possible from the implementation of a co-teaching model within a middle level education program. Benefits of co-teaching for middle level teacher candidates, classroom teachers, and university faculty are included. The results of this study may provide a unique framework of co-teaching which enhances interactions among educational constituents for improved teacher preparation, professional development for practicing teachers, and improved instruction for middle grades students.
Keywords: co-teaching; partnerships; middle level teacher education; teacher preparation